Tanzania: Agricultural R&D indicators factsheet update - Beintema, Nienke M.; Lwezaura, Deogratias; Munishi, Bernadetha (International Food Policy Research Institute, 2018)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also feature a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.